Impact of Online Consumer Reviews on Buying Intention of Consumers in UK: Need for Cognition as the Moderating Role - Obiedat, Ruba (International Journal of Advanced Corporate Learning (iJAC), 2013)
World wide web has offered a strong competitive platform for online marketing which turned out the online shopping important for consumers in todayâ??s world particularly those consumers which view the online reviews as effectual conduit of having important product information prior to purchasing decisions. However, the current study attempts to find the impact of online consumer reviews on buying intention of consumers in the context of UK with need for cognition as the mediating role on the basis of elaboration likelihood model developed in 2011. This study followed positivist research philosophy by using quantitative data from 120 consumers in UK who shop online. In conclusion, the current study demonstrated that the buying intention of online consumer who has high cognitive needs was affected by quality of online review or argument as compare to quantity of online argument or reviews. Furthermore, the buying intentions of online consumers with low cognitive need were affected by quantity of rather than quality of arguments. Therefore, hypothesis of current were supported.